Metformin Resensitizes Sorafenib-Resistant HCC Cells Through AMPK-Dependent Autophagy Activation - Lai, Hong-Yue; Tsai, Hsin-Hwa; Yen, Chia-Jui; Hung, Liang-Yi; Yang, Ching-Chieh; Ho, Chung-Han; Liang, Hsin-Yin; Chen, Feng-Wei; Li, Chien-Feng; Wang, Ju-Ming (Frontiers in Cell and Developmental Biology, 2021)
Despite the activation of autophagy may enable residual cancer cells to survive and allow tumor relapse, excessive activation of autophagy may eventually lead to cell death. However, the details of the association of autophagy with primary resistance in hepatocellular carcinoma (HCC) remain less clear. In this study, cohort analysis revealed that HCC patients receiving sorafenib with HBV had higher mortality risk. We found that high epidermal growth factor receptor (EGFR) expression and activity may be linked to HBV-induced sorafenib resistance. We further found that the resistance of EGFR-overexpressed liver cancer cells to sorafenib is associated with low activity of AMP-activated protein kinase (AMPK) and CCAAT/enhancer binding protein delta (CEBPD) as well as insufficient autophagic activation. In response to metformin, the AMPK/cAMP-response element binding protein (CREB) pathway contributes to CEBPD activation, which promotes autophagic cell death. Moreover, treatment with metformin can increase sorafenib sensitivity through direct AMPK activation in EGFR-overexpressed liver cancer cells. This study suggests that AMPK/CEBPD-activated autophagy could be a potent strategy for improving the efficacy of sorafenib in HCC patients.